Nanotechnologies for the Life Sciences 2003
DOI: 10.1002/9783527610419.ntls0055
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Environmental Remediation

Abstract: The sections in this article are Introduction Nanoparticle‐based Remediation Materials Acid–Base Chemistry Redox Chemistry Field Deployments of ZVI Absorption Chemistry Hybrid Nanostructured Remediation Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…Ma et al [51] confirmed these results and stated that cells accumulating Si significantly reduce the net Cd 2+ influx compared to cells not treated with Si. Nanotechnology offers a further approach to metal remediation through the design and use of micron-or nano-size metal-binding polymer particles with very high specific surface area [52] and high reactivity [53]. In this context, Cui et al [54] studied the impact of silica nanoparticles (SiNPs) on the attenuation of Cd toxicity in rice using a cell suspension culture and found that the presence of SiNPs allowed cells to remain almost intact even with high concentrations of Cd.…”
Section: Siliconmentioning
confidence: 99%
“…Ma et al [51] confirmed these results and stated that cells accumulating Si significantly reduce the net Cd 2+ influx compared to cells not treated with Si. Nanotechnology offers a further approach to metal remediation through the design and use of micron-or nano-size metal-binding polymer particles with very high specific surface area [52] and high reactivity [53]. In this context, Cui et al [54] studied the impact of silica nanoparticles (SiNPs) on the attenuation of Cd toxicity in rice using a cell suspension culture and found that the presence of SiNPs allowed cells to remain almost intact even with high concentrations of Cd.…”
Section: Siliconmentioning
confidence: 99%